Correlation between pain severity and levels of anxiety and depression in osteoarthritis patients: a systematic review and meta-analysis. (21st June 2021) - Fonseca-Rodrigues, Diana; Rodrigues, André; Martins, Teresa; Pinto, Joana; Amorim, Diana; Almeida, Armando; Pinto-Ribeiro, Filipa
Abstract: Objectives: Osteoarthritis (OA) is a chronic degenerative musculoskeletal disease that causes articular damage and chronic pain, with a prevalence of up to 50% in individuals >60 years of age. Patients suffering from chronic painful conditions, including OA, also frequently report anxiety or depression. A systematic review and meta-analysis were performed to assess the correlation between pain severity and depressive and anxious symptomatology in OA patients. Methods: A systematic search was conducted using four databases (PubMed, Medline, Scopus, and Web of Science) from inception up to 14 January 2020. We included original articles evaluating pain severity and anxiety and/or depression severity in OA-diagnosed patients. Detailed data were extracted from each study, including patients' characteristics and pain, anxiety, and depression severity. When available, the Pearson correlation coefficient between pain and depression severity and pain and anxiety severity was collected, and a meta-analysis of random effects was applied. Results: This systematic review included 121 studies, with a total of 38 085 participants. The mean age was 64.3 years old, and the subjects were predominantly female (63%). The most-used scale to evaluate pain severity was the Western Ontario and the McMaster Universities Osteoarthritis Index, while for anxiety and depression, the Hospital Anxiety and Depression Scale was the most used. The meta-analysis showed a moderate positive correlation between pain severity and both anxious ( r  = 0.31, P <0.001) and depressive symptomatology ( r  = 0.36, P <0.001). Conclusion: Our results demonstrate a significant correlation between pain and depression/anxiety severity in OA patients, highlighting the need for its routine evaluation by clinicians.